Temperature Dependence of Ionic Conductivity of Ceria Electrolyte at Concentrated Range of Multiple Doping. Issue 9 (13th May 2013) - Panigrahi, Snigdha; Biswal, Ramesh Chandra; Anwar, Shahid; Besra, Laxmidhar; Bhattacharjee, Sarama; Wei, W.‐C.
<x xml:space="preserve">Abstract</x> We study ionic conductivity of heavily doped ceria, doping level close to 50 mol% with multiple lanthanides in the temperature range of 200°C–500°C. The doped ceria is found to be single fluorite phase, where unit cell is dilated to 0.5527 nm, compared with pure ceria (0.5422 nm). Electrical characterization by impedance spectroscopy reveals that sample sintered at lower temperature (1400°C) has consistently higher bulk conductivity compared to sample sintered at higher (1600°C) temperature, throughout the temperature range studied. Activation energy for oxygen vacancy diffusion is close to 1 eV, indicating lesser association of defects with the dopants compared with other heavily doped ceria reported in literature (activation energy ~1.4 eV). The best ionic conductivity is found to be 1.58 × 10−3 S/cm at 500°C, which is much higher compared with heavily doped ceria reported in literature.